Działalność misjonarska św. Piotra poza Palestyną w świetle literatury nowotestamentowej - Mickiewicz, Franciszek (Collectanea Theologica, 2019)
In this article an attempt is made at answering the question of where Peter was able to stay and act. It considers the time from when Peter left Jerusalem in the year 42 (Acts 12:17) to his arrival in Rome. The analysis of Galatians 2:11-14 leads to the conclusion that after the Jerusalem Council he certainly spent some time in Antioch. It is possible that during his many years of travel he reached the northern regions of Asia Minor. We find reminiscence of this in 1 Peter 1:1. Later, on the way to Rome, he probably visited Christians in Corinth as can be seen in 1 Corinthians 12:9,5. These texts allow the supposition that, after leaving Jerusalem, Peter became an itinerant apostle, led extensive missionary activity, and, through personal contacts with Christian communities, obtained great authority among them.